Atypical communication characteristics among clinic-referred youth with and without autism spectrum disorder: Stability and associations with clinical correlates. (October 2020) - Kang, Erin; Lerner, Matthew D.; Gadow, Kenneth D.
Abstract: Atypical communication characteristics (ACCs), such as speech delay, odd pitch, and pragmatic difficulties, are common features of autism spectrum disorder (ASD) as are the symptoms of a wide range of psychiatric disorders. Using a simple retrospective method, this study aimed to better understand the relation and stability of ACCs with a broad range of psychiatric symptoms among large, well-characterized samples of clinic-referred children and adolescents with and without ASD. Youth with ASD had higher rates and a more variable pattern of developmental change in ACCs than the non-ASD diagnostic group. Latent class analysis yielded three ACC stability subgroups within ASD: Stable ACCs, Mostly Current-Only ACCs, and Little Professors. Subgroups exhibited differences in severity of ASD symptomatology, co-occurring psychiatric symptoms, and other correlates. Our findings provide support for the clinical utility of characterizing caregiver-perceived changes in ACCs in identifying children at risk for co-occurring psychopathology and other clinically relevant variables.